PENGARUH NEGARA ASAL, CITRA MEREK, DAN PERSEPSI KUALITAS TERHADAP MINAT BELI SEPEDA MOTOR YAMAHA VIXION DI KOTA YOGYAKARTA - Nandia Anggraini; Fitroh Adhilla (Universitas Ahmad Dahlan, 2017)
This study was conducted to determine the effect of country of origin, brand image, and perceived quality of purchase interest in Yamaha V-Ixion motorbikes in Yogyakarta City, samples taken were 100 respondents using non-probability sampling methods with purposive sampling technique. Data collection techniques using a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression analysis. The results of this study indicate that: (1) There is no significant influence between the country of origin variables on buying interest; (2) There is a significant influence between brand image variables on buying interest; (3) There is a significant influence between perceived quality variables on buying interest; and (4) country of origin, brand image, and perceived quality simultaneously influence buying interest.